DAMPAK PERSAINGAN DAN DUKUNGAN KELUARGA DALAM PENINGKATAN MOTIVASI PERAWAT MELANJUTKAN PENDIDIKAN - Agustina, Eliza; Meri, Dilgu; Ekaputri, Mersi; Fadhli, Rohmi (Jurnal Keperawatan Karya Bhakti, 2025)
Nurses' motivation to continue their education is an important aspect in developing professionalism and improving the quality of health services. Motivation to develop their abilities, in providing nursing care requires nurses with advanced education. Objective: The purpose of this study was to determine the relationship between competition and family support with nurses' motivation to continue their education at Aulia Hospital Pekanbaru 2025. Method: Quantitative research type with cross-sectional design. The population of this study were all DIII nurses at Aulia Hospital Pekanbaru as many as 60 people. The sampling technique used was total sampling. The study was conducted from September 2024 to March 2025. Data collection using a questionnaire was then analyzed univariately and bivariately with a normality test obtained data that was not normal statistical test and using chi square. Conclusion: The results of the univariate analysis obtained as many as 49 people in early adulthood, 50 female gender. A total of 36 nurses said that there was high competition in continuing their education and 24 people said that there was low competition in continuing their education. Bivariate analysis found that there was a significant relationship between competition and nurses' motivation to continue their education with a p value (0.020) <0.05 and there was a relationship between family support and nurses' motivation to continue their education with a p value (0.000) <0.05. Keywords: Family support; Motivation; Nurse; Education; Competition.